Effects of the 15-methyl analogs of prostaglandins E2 and F2alpha on the pulmonary circulation in the intact dog. - Kadowitz, P J (1975)
The effects of the 15-methul analogs of prostaglandins E2 (PGE2) and F2alpha (PGF2alpha) on the pulmonary circulation were studied in the intact dog under conditions of controlled blood flow. Infusions of either analog into the lobar artery increased lobar arterial pressure by more than 100 per cent. The rise in lobar arterial pressure was accompanied by a rise in lobar venous pressure and in pressure gradient from lobar artery to small vein but no change in pressure in the left atrium. The methyl analogs were about 10 times more potent than PGE2 and PGF2alpha in elevating pulmonary vascular resistance in the dog. The effects of the analogs on the pulmonary vascular bed were similar in experiments in which the lung was perfused with dextran or with blood. Both analogs contracted isolated helical segments of canine intrapulmonary artery and vein in a dose-related manner. In other experiments the effects of passive increases in venous pressure produced by distension of a balloon catheter in the lobar vein were contrasted with the action of the analogs on the pulmonary vascular bed. Balloon distension increased pressure in the lobar artery and small vein but had no effect on pressure in the left atrium. However, in contrast to the increase in gradient with the analogs, balloon distension decreased the pressure gradient from lobar artery to small vein. Results of the present study indicate that the prostaglandin analogs increase pulmonary vascular resistance by actively contricting pulmonary veins and vessels upstream to small veins, presumed to be small arteries. It is concluded that the analogs are potent pressor substances in the pulmonary circulation.